2020
DOI: 10.1016/j.jgo.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The association between the inflammatory response to surgery and postoperative complications in older patients with cancer; a prospective prognostic factor study

Abstract: Background: Accurate prognostic biomarkers would substantially improve surgical planning and decisions making yet no studies have been reported exploring the inflammatory response in surgically treated older patients with cancer. The aim of this study was to explore inflammatory biomarkers as potential prognostic factors for postoperative complications within 30 days in older patients with cancer. Method: Patients 65 years and older undergoing surgery for removal of a solid malignant tumour were included in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…We also found that increases in IL-6 and YKL-40 during the first and second days following surgery were associated with major complications. An association between postoperative complications and the early increase in IL-6 on the first postoperative day [ 38 ] and immediately after surgery [ 39 ] has been demonstrated, but the association has not been investigated for YKL-40. The relationship between postoperative systemic inflammation and major complications is expected, since many complications have an inflammatory component (e.g., anastomotic leak) and other studies have shown that high CRP on postoperative days three and four is associated with anastomotic leak [ 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that increases in IL-6 and YKL-40 during the first and second days following surgery were associated with major complications. An association between postoperative complications and the early increase in IL-6 on the first postoperative day [ 38 ] and immediately after surgery [ 39 ] has been demonstrated, but the association has not been investigated for YKL-40. The relationship between postoperative systemic inflammation and major complications is expected, since many complications have an inflammatory component (e.g., anastomotic leak) and other studies have shown that high CRP on postoperative days three and four is associated with anastomotic leak [ 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data for this observational cohort study were prospectively collected in the setting of an observational cohort study conducted in the University Medical Center Groningen (UMCG) as described elsewhere. 11,[32][33][34] Patients were included from April 2014 till October 2016 following a previously determined study protocol. Eligible for inclusions were all patients, aged 18 years and older, who received elective oncological surgery in the UMCG, regardless of the primary tumor.…”
Section: Study Populationmentioning
confidence: 99%
“…Blood samples were handled as described previously. 33 All blood samples were directly centrifuged at 26009g for 10 min, after which they were stored at a minimum of -80 °C. All blood was analyzed for C-reactive protein (CRP) (lower limit of detection [LLD]: 0.001 lg/ml), interleukin-1b (IL-1b) (LLD: 1.27 pg/ml), IL-6 (LLD: 0.01 pg/ml), IL-10 (LLD: 3,28 pg/ml), IL-12 (LLD: 5.07 pg/ml), and tumor necrosis factor-alpha (TNF-a) (LLD: 6.49 pg/ml).…”
Section: Blood Sampling and Biochemical Analysismentioning
confidence: 99%
“… 1 Formatting...Recently, systemic inflammation also has been found to be a predictor of complications, as evidenced by elevated levels of inflammatory cytokines, such as IL-6, IL-8, and IL-10. 2 …”
Section: Pastmentioning
confidence: 99%